PENURUNAN JUMLAH KOLONI STREPTOCOCCUS MUTANS DALAM RONGGA MULUT OLEH EKSTRAK ETANOL KULIT DAUN LIDAH BUAYA - Armiati, I Gusti Ketut (Faculty of Dentistry, Mahasaraswati Denpasar University, 2018)
Dental plaque is a soft deposit which is firmly attached to the tooth surface. Streptococcus, Staphilococcus, Lactobacillus, and filaments form bacteria are microorganisms that can often be isolated from caries lesions and inflammation of the oral mucosa. Chlorhexidine gluconate is one of the antimicrobial agents become the gold standard in dentistry for the prevention of dental plaque. The aims of this study is to determine the effectiveness of rinsing with aloe vera skin leaf extract (Aloe vera barbadensis miller) in reducing the number of Streptococcus mutans in the oral cavity. Experimental studies with randomized pretest-posttest control group design, involving 30 patients,were divided into three (3) groups: the negative control group were rinsed with distilled water, the positive control group were rinsed with chlorhexidine gluconate 0.2%, and the treatment group were rinsed with 100% aloe vera leaves extract. After treatment, analyzed by One Way ANOVA it was found decrease the number of S. mutans bacteria colonies in the positive control group and the treatment group after treatment (p<0.05). While the negative control group did not decrease significantly. The conclusions of this study is rinsing with 100% aloe vera skin leaf extract decrease the number of Streptococcus mutans bacteria colonies by 55.57%.